Does duration of donor brain injury impact heart transplantation outcomes?. Issue 8 (22nd July 2019) - Kogan, Alexander; Ram, Eilon; Nachum, Eyal; Kassif, Yigal; Lavee, Jacob; Peled, Yael
Abstract: Aim: We aimed to study the implications of pre‐transplantation time intervals on HT outcomes. Methods: Brain injury time (BIT) was defined as the period from the donor brain injury to brain death declaration. Brain death interval (BDI) was defined as the period from brain death to application of an aortic cross‐clamp during donor heart procurement. Allograft ischemia was defined as the time from donor aortic cross‐clamp to aortic unclamping. End points included mortality and rejections. Results: Between 1997 and 2017, we assessed 173 patients. Kaplan‐Meier analyses showed that prolonged donor BIT, BDI, allograft ischemia, and total injury time had no significant effect on mortality and rejections. Patients were subdivided into short BIT (<97 hours, n = 87) and long BIT (≥97 hours, n = 86) groups. No differences in rejection scores nor in time to first rejection were noted. Kaplan‐Meier analysis showed a similar long‐term survival in the two groups. Sub‐analysis of both groups according to their median BDI (12 hours) revealed no differences in mortality or time to rejection. Conclusions: Pre‐transplantation time intervals do not affect mortality or rejection. Our findings have important clinical implications regarding HT allocation and organ availability.